PENERAPAN PROJECT BASED LEARNING DALAM PEMBELAJARAN DI SEKOLAH DASAR - Badruli Martati (Universitas Muhammadiyah Surabaya, 2022)
The Independent Curriculum gives teachers freedom to choose various teaching tools so that learning can be adapted to the needs of learning and the interests of learners. One of the recommended learning models is Project Based Learning (PjBL) which is a learning activity in the form of making goods or services that are used as a vehicle for mastering competencies. The purpose of research how did a description of elementary school/mi Muhammadiyah teacher's knowledge in Surabaya about Project Based Learning? Approaches to the phenomenon, data processing is implemented with a descriptive data analysis strategy. Studies show that there are many teachers who do not understand correctly. Thus it is necessary to have a workshop in order for understanding and will to implement project based learning (PJBL), which is different from the model learning Problem Based Learning that has been adopted by Muhammadiyah elementary school/mi teachers.Â Keywords: Learning Model, Project Based Learning, Elementary School